Disaster preparedness and well-being among Cambodian– and Laotian–Americans. Issue 4 (17th September 2019) - DeYoung, Sarah E.; Lewis, Denise C.; Seponski, Desiree M.; Augustine, Danielle A.; Phal, Monysakada
Abstract : Purpose: Using two main research questions, the purpose of this paper is to examine well-being and preparedness among Cambodian and Laotian immigrants living near the Gulf Coast of the USA, and the ways in which indicators such as sense of community and risk perception are related to these constructs. Design/methodology/approach: This study employed a cross-sectional prospective design to examine disaster preparedness and well-being among Laotian and Cambodian immigrant communities. Quantitative survey data using purposive snowball sampling were collected throughout several months in Alabama, Mississippi, Florida and Louisiana. Findings: Results from two multiple regressions revealed that sense of community and age contributed to well-being and were significant in the model, but with a negative relationship between age and well-being. Risk perception, confidence in government, confidence in engaging household preparedness and ability to cope with a financial crisis were significant predictors and positively related to disaster preparedness. Practical implications: Well-being and disaster preparedness can be bolstered through community-based planning that seeks to address urgent needs of the people residing in vulnerable coastal locations. Specifically, immigrants who speak English as a second language, elder individuals and households in the lowest income brackets should be supported in disaster planning and outreach. Originality/value: Cambodian and Laotian American immigrants rely upon the Gulf Coast's waters for fishing, crab and shrimp income. Despite on-going hazard and disasters, few studies address preparedness among immigrant populations in the USA. This study fills a gap in preparedness research as well as factors associated with well-being, an important aspect of long-term resilience.